2022
DOI: 10.3390/ijerph19095056
|View full text |Cite
|
Sign up to set email alerts
|

Shared Virtual Reality Experiences during the COVID-19 Pandemic: Exploring the Gratifications and Effects of Engagement with Immersive Videos

Abstract: The coronavirus (COVID-19) pandemic and recent economic recession have been impacting many people’s mental health. The experience of social distancing created new hardships for people who already reported symptoms of depression or anxiety. In these circumstances, new technologies, such as immersive virtual reality (VR) videos, could serve as useful tools for facilitating interactions, emotional sharing, and information processing within a virtual environment. In this study, researchers aimed to enrich the info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
1
7
0
1
Order By: Relevance
“…In other words, it was confirmed that the experience of space and exchange provided by the metaverse that is similar to the real organization could increase the intention of continuous use by influencing the employees' motivation to use it. The results are similar to those of Fu et al [33] and Han et al [14], as the presence factor provided by the online platform increases the gratification of users' needs and induces positive behavior on the platform. Therefore, organizations must provide virtual reality technology for the metaverse platform in order to make it possible to feel that the exchange of information and interaction activities take place realistically and offer an entertainment element equipped with a sense of reality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, it was confirmed that the experience of space and exchange provided by the metaverse that is similar to the real organization could increase the intention of continuous use by influencing the employees' motivation to use it. The results are similar to those of Fu et al [33] and Han et al [14], as the presence factor provided by the online platform increases the gratification of users' needs and induces positive behavior on the platform. Therefore, organizations must provide virtual reality technology for the metaverse platform in order to make it possible to feel that the exchange of information and interaction activities take place realistically and offer an entertainment element equipped with a sense of reality.…”
Section: Discussionsupporting
confidence: 88%
“…Han et al [14] confirmed that the social presence provided by social media increases the intention to use the platform continuously through the gratification of social connection needs. Fu et al [33] found that the virtual presence of social media is a hedonic gratification. It was confirmed that self-disclosure has increased in relation to virtual reality, and the sense of presence affects the formation of user motivation.…”
Section: Telepresence Of the Metaversementioning
confidence: 99%
“…Since the outbreak of the ongoing pandemic, the discussion and efforts surrounding digitalization have increased unprecedently. Almost every entity, whether affiliated to the state, society, or economy, has been working tirelessly to establish a virtual presence (Cheng, Wang, and Zhao 2022). The intergovernmental institutions have not been an exception and in some cases, they have been leading the way.…”
Section: Expansion Of the Virtual Worldmentioning
confidence: 99%
“…Media and social conversations were dominated by large amounts of information about COVID-19, of which there was initially little known. Public health information communicated through social networks and traditional media was inconsistent, and messages conveyed were sometimes not well-received (Cheng et al, 2022;Clemente-Suárez et al, 2022). America's vast size and decentralized governance structure resulted in uneven implementation of often-conflicting recommendations coming from epidemiologists, media influencers and government officials.…”
Section: Communicationmentioning
confidence: 99%